PERANCANGAN KAWASAN CAGAR BUDAYA TAMBANG ORANJE NASSAU - Prananda Ristyani Fadillah; Muhammad Deddy Huzairin (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
Orange Nassau is a Dutch heritage coal mine site that has been established since 28 September 1849. Which is the starting place where the Banjar war started. This site is also known as the oldest coal mine site in Kalimantan Selatan and even Indonesia. Unfortunately, the existing site condition is not maintained well and less known for what it actually is. Therefore, this site needs “Design of Orange Nassau Cultural Heritage Area” as an architecture solution, to protect its heritage, embracing its historical background and developing its potential. The method that was used for the design is Conservation Revitalization method: Adaptive Re-use, this method aims to conserve the Orange Nassau heritage with new function adjustment. In specific, giving this area an educative and recreation facilities with enchanting architectural ways. Sense of place is also used as the concept. Which has meaning as making a place where emotional bonding between place and human can rhyme together. In conclusion, this design is about conserving the heritage site and maintaining the authenticity of colonial architecture with the concept that is applied.